First‐Line Antiarrhythmic Transplacental Treatment for Fetal Tachyarrhythmia: A Systematic Review and Meta‐Analysis. Issue 12 (15th December 2017) - Alsaied, Tarek; Baskar, Shankar; Fares, Munes; Alahdab, Fares; Czosek, Richard J; Murad, Mohammad Hassan; Prokop, Larry J; Divanovic, Allison A
Abstract : Background: There is no consensus on the most effective and best tolerated first‐line antiarrhythmic treatment for fetal tachyarrhythmia. The purpose of this systematic review and meta‐analysis was to compare the efficacy, safety, and fetal–maternal tolerance of first‐line monotherapies for fetal supraventricular tachycardia and atrial flutter. Methods and Results: A comprehensive search of several databases was conducted through January 2017. Only studies that made a direct comparison between first‐line treatments of fetal tachyarrhythmia were included. Outcomes of interest were termination of fetal tachyarrhythmia, fetal demise, and maternal complications. Ten studies met inclusion criteria, with 537 patients. Overall, 291 patients were treated with digoxin, 137 with flecainide, 102 with sotalol, and 7 with amiodarone. Digoxin achieved a lower rate of supraventricular tachycardia termination compared with flecainide (odds ratio [OR]: 0.773; 95% confidence interval [CI], 0.605–0.987; I 2 =34%). In fetuses with hydrops fetalis, digoxin had lower rates of tachycardia termination compared with flecainide (OR: 0.412; 95% CI, 0.268–0.632; I 2 =0%). There was no significant difference in the incidence of maternal side effects between digoxin and flecainide groups (OR: 1.134; 95% CI, 0.129–9.935; I 2 =80.79%). The incidence of maternal side effects was higher in patients treated with digoxin compared with sotalol (OR: 3.148; 95% CI, 1.468–6.751; I 2 =0%). There was no difference in fetal demise between flecainide and digoxin (OR: 0.767; 95% CI, 0.140–4.197; I 2 =44%). Conclusions: Flecainide may be more effective treatment than digoxin as a first‐line treatment for fetal supraventricular tachycardia.